Performance comparison of core loss in induction motor using non-oriented electrical steels - Reddy, Chittimilla Shravan Kumar; Arivukkannu, Ezhilarasi; Jayaraman, Kartigeyan (Institute of Advanced Engineering and Science, 2025)
Induction motor (IM) enjoy certain advantages that include simple design, robust construction, reliable operation, low initial cost, easy operation and simple maintenance besides offering reasonable efficiency. Modelling and definition of procedures leading to good estimation of core losses in induction motors from material test data is still a challenge, is considered as problem statement. The major objective of this paper is to estimate the core loss in an induction motor (IM) by analyzing a selection of non-grain oriented electrical steel materials and then identifying for each represented whether it can be used both as stator and rotor core material. As core loss is influenced by factors such as air gap, B-H theory, eddy currents and excess loss coefficients and Steinmetzuhl factor, this study is intended to improve the electromagnetic performance of the motor. Influencing core loss are the amounts of flux density and elasticity of material. This study was accomplished by using three sorts of non oriented electrical steel: DI MAX-M15, DI MAX-M19, and DI MAX-M36. A 5 HP induction motor was the subject for finite element method (FEM) simulations whose results have been verified by empirical relations, which show the merit of using non oriented electrical steel as core material.